Self-Reported Versus Digitally Recorded: Measuring Political Activity on Facebook. (October 2020) - Haenschen, Katherine
Facebook has been credited with expanding political activity by simultaneously lowering barriers to participation and creating new ways to engage. However, many of these findings rely on subjects' abilities to accurately report their Facebook use and political activity on the platform. This study combines survey responses and digital trace data from 828 American adults to determine whether subjects over- or underreport a range of political activities on Facebook, including whether they like political pages or share news links. The results show that individuals underestimate their frequency of status posting and overestimate their frequency of sharing news links on Facebook. Political interest is associated with a decrease in underreporting several political activities, while increasing the likelihood of overreporting the frequency of sharing news links. Furthermore, political interest serves a moderating effect, improving self-reports for high-volume users. The findings suggest that political interest not only predicts political activity but also shapes awareness of that activity and improves self-reports among heavy users.